A new class of BFGS updating formula based on the new quasi-newton equation - Basim Abbas Hassan; Hussein K. Khalo (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Quasi-Newton methods” are amongst the mainly useful and competent iterative process for solving unrestrained minimization functions. In this paper we derive a new quasi-Newton equation with on the Hessian estimate updates and alterations intended at developing their performance. The “Numerical results” illustrate that the proposed technique useful for the known test functions.